2000
DOI: 10.1002/1097-4628(20001114)78:7<1419::aid-app130>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of twin-screw extrusion of polypropylene

Abstract: The flow of a polypropylene in a self‐wiping corotating twin‐screw extruder was characterized by measuring the pressure, temperature, and residence time along the screw profile. The influence of the operating conditions (feed rate, screw speed, barrel temperature) and screw profile was studied. Flow modeling was performed using the Ludovic© software and measured and calculated pressure, temperature, residence time, and energy consumption were compared. The values of the temperature close to the melting zone we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(16 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…It is quite independent of the feed mass and decreases slightly with the temperature (not shown). The order of magnitude is similar to those encountered in usual extrusion processes: for example, depending on processing conditions, Carneiro et al [ 17 ] measured SME between 170 and 370 kWh/t on a Leistritz extruder (34 mm in diameter), and Berzin et al [ 18 ] reported values in the range 200–800 kWh/t on a Clextral extruder (25 mm in diameter). Our values are also in agreement with those reported by Decaen et al [ 13 ] for thermoplastic starch extruded on the same type of micro‐compounder: 125 kWh/t at 100 rpm during 5 min, corresponding to 25 kWh/t for 1 min, which is what we can see in Figure 2C.…”
Section: Experimental Studysupporting
confidence: 60%
“…It is quite independent of the feed mass and decreases slightly with the temperature (not shown). The order of magnitude is similar to those encountered in usual extrusion processes: for example, depending on processing conditions, Carneiro et al [ 17 ] measured SME between 170 and 370 kWh/t on a Leistritz extruder (34 mm in diameter), and Berzin et al [ 18 ] reported values in the range 200–800 kWh/t on a Clextral extruder (25 mm in diameter). Our values are also in agreement with those reported by Decaen et al [ 13 ] for thermoplastic starch extruded on the same type of micro‐compounder: 125 kWh/t at 100 rpm during 5 min, corresponding to 25 kWh/t for 1 min, which is what we can see in Figure 2C.…”
Section: Experimental Studysupporting
confidence: 60%
“…The simulation is based on a onedimensional analysis. The screws are divided into elementary For 20 years, the Ludovic R software has been extensively validated, experimentally (Carneiro et al, 2000) and by comparisons with more elaborate 3D models (Durin et al, 2014).…”
Section: Flow Modelingmentioning
confidence: 99%
“…Although scale-up studies via HME processes in the plastics industry is designed for high-throughput products up to 50 tons/h, the laboratory scale in pharmaceutical and/or plastic research is related to extruder sizes of approximately 30 mm in screw diameter, which translates into feed rates of approximately 4-6 kg/h [75][76][77][78]. Recently, Zeceivic et al reported a numeric process simulation-based scale-up study via HME processing using process data as well as rheological and thermal properties of the formulations.…”
Section: Scale-up Applications Via Hmementioning
confidence: 99%